Spotted Fever Group Rickettsiae among Children with Acute Febrile Illness, in Gorakhpur, India. (30th June 2020) - Khan, Siraj A; Bora, Trishna; Thangaraj, Jeromie Wesley Vivian; Murhekar, Manoj V
Abstract: Seasonal outbreaks of acute encephalitis syndrome have been occurring in Gorakhpur division in the Indian state of Uttar Pradesh during monsoon and post-monsoon months. Orientia tsutsugamushi was identified as the major aetiology of these outbreaks. Orientia tsutsugamushi was also identified as one of the important aetiology of febrile illness among children attending peripheral health facilities. The present study was undertaken to detect antibodies against spotted fever group rickettsiae (SFGR) and typhus group rickettsiae (TGR) among children with acute febrile illness presenting at peripheral health facilities in Gorakhpur district. Of the 224 blood samples tested, SFGR infection was detected in 13 (6%) patients. None of the samples tested positive for TGR.